A dictionary of geography - Mayhew, Susan (Oxford University Press Oxford [England], 1997)
"This unique new dictionary offers comprehensive coverage of words and terms encountered in both human and physical geography in a single volume. Each of the over 6,000 updated, clear, and concise entries provides an initial brief definition followed by a more in-depth explanation, making the book useful for novices and experts alike. This new edition also features a fact-finder with key economic and population statistics." "Authoritative and completely accessible, A Dictionary of Geography, Second Edition covers a vast scope of subjects, including cartography, surveying, meteorology, climatology, biogeography, ecology, geology, geomorphology, population, migration, agriculture, industry, transportation, and development. There is also extensive discussion of the most recent advances in and information on topics such as plate tectonics, remote sensing, geographic information systems, and aerial differentiation." "Wide-ranging and highly readable, this invaluable reference guide answers questions about all aspects of geography quickly and effectively using the most recent advances in the field."--Jacket